ANXIETY LEVEL IN ENGLISH SPEAKING AMONG AHMAD DAHLAN STUDENTS - Megawati Basri; Fahmi Djaguna; Balqis Husain (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2020)
One language that is a communication tool in various parts of the world is English; English has become a language that must be mastered by the community, especially students. However, not everyone can easily speak English. The purpose of this research is to know the level of anxiety when they speak in English at Universitas Ahmad Dahlan students. This research uses a qualitative method. One hundred and twenty seven students were selected as the participants of the questionnaire; the tool used for this study was adapted from Horwitz, Horwitz & Cope (1986) Foreign Language Classroom Anxiety Scale (FLCAS). The result of this study was showed that the majority of the students (n=103) were found students had a moderate level of anxiety, one student had a very high level of anxiety and thirteen students were found to had a high level of anxiety. The level of anxiety by dimensions, such as the Fear of Negative Evaluation (FNE) ranks third. Meanwhile, Communication Apprehension (CA) and Test Anxiety (TA) are significantly dominant performance anxieties.